RNA Binding Motif 5 (RBM5) in the CNS—Moving Beyond Cancer to Harness RNA Splicing to Mitigate the Consequences of Brain Injury - Jackson, Travis C.; Kochanek, Patrick M. (Frontiers in Molecular Neuroscience, 2020)
Gene splicing modulates the potency of cell death effectors, alters neuropathological disease processes, influences neuronal recovery, but may also direct distinct mechanisms of secondary brain injury. Therapeutic targeting of RNA splicing is a promising avenue for next generation CNS treatments. RNA-binding proteins (RBPs) regulate a variety of RNA species and are prime candidates in the hunt for druggable targets to manipulate and tailor gene splicing responses in the brain. RBPs preferentially recognize unique consensus sequences in targeted mRNAs. Also, RBPs often contain multiple RNA-binding domains (RBDs) - each having a unique consensus sequence - suggesting the possibility that drugs could be developed to block individual functional domains, increasing the precision of RBP-targeting therapies. Empirical characterization of most RBPs is lacking and represents a major barrier to advance this emerging therapeutic area. There is a paucity of data on the role of RBPs in the brain including, identification of their unique mRNA targets, defining how CNS insults effect their levels, and elucidating which RBPs (and individual domains within) to target to improve neurological outcomes. This review focuses on the state-of-the-art of the RBP tumor suppressor RNA binding motif 5 (RBM5) in the CNS. We discuss its potent pro-death roles in cancer, which motivated our interest to study it in the brain. We review recent studies showing that RBM5 levels are increased after CNS trauma and that it promotes neuronal death in vitro. Finally, we conclude with recent reports on the first set of RBM5 regulated genes identified in the intact brain, and discuss how those findings provide new clues germane to its potential function(s) in the CNS, and pose new questions on its therapeutic utility to mitigate CNS injury.